Challenges of Translating Cultural Terms in Jumla: A Nurse Story - Khadka, Dharmaraj (Janajyoti Journal, 2025)
This paper seeks to explore the challenges in translating culture-specific terms in Jumla: A Nurse Story, the English rendition of Radha Poudel’s acclaimed Nepali narrative Khalanga Ma Hamala. The study critically examines how the translator has dealt with culturally loaded words, ecological references, social customs, material objects, and administrative terminology in the context of Jumla, a remote district in Nepal. Drawing on key translation theories by Peter Newmark, Juliane House, and Clifford E. Landers, the paper analyzes various translation techniques such as adaptation, deletion, neutralization, interpolation, and functional equivalence, and their effects on meaning, tone, and cultural authenticity. The translated text is examined for fidelity to the original’s emotional intensity, cultural embeddedness, and narrative flow. Particular attention is given to problematic translations, such as the misrepresentation or omission of Nepali ecological and religious terms. They often dilute the source text’s richness. The paper concludes that while the translation successfully bridges linguistic gaps, it also compromises cultural integrity in certain areas which is relevant for translators, cultural theorists, and scholars working on Nepali literature in translation. It aims to contribute to the growing body of research on literary translation and cross-cultural communication, especially from minoritized languages to English.